درجة ممارسة المعلّمين الأوائل للإشراف المتنوع في في سلطنة عمان وعلاقتها بالأداء المهني لمعلمي التربية الإسلامية - سعيدي، محمد سالم راشد (Kulliyah of Education, International Islamic University Malaysia, 2021)
The study aimed to examine the level of diversified supervision among Islamic Education senior teachers in the Sultanate of Oman from the perspectives of Islamic Education teachers and educational supervisors. It also aimed to identify the levels of professional performance of Islamic Education teachers' from the perspectives of senior teachers and educational supervisors, and to examine the relationship between the diversified supervision and Islamic Education teachers' professional performance. Finally, it explored the obstacles facing the implementation of diversified supervision. The study utilized the mixed method approach that combined the quantitative and qualitative methods. Two developed questionnaires were used to collect data from the study sample which consisted of (263) teachers, (124) senior teachers and (35) supervisors; and face-to-face interviews were conducted with (8) senior Islamic Education teachers. Quantitative data were analyzed using the Statistical Package for Social Sciences (SPSS) and Statistical Program (SMART-PLS), and qualitative data were analyzed using (Thematic Analysis). The study found that the level of diversified supervision among Islamic education senior teachers was high, with means ranged from (3.57-3.90). The cooperative supervision got the highest mean, followed by the intensive development supervision, and self-professional development supervision. It also found that there were no statistically significant differences in the levels of diversified supervision among Islamic Education senior teachers due to position or experience. Furthermore, it indicated that the level of professional performance of Islamic education teachers was high, (M = 3.76). There was a direct positive relationship between the level of diversified supervision among Islamic Education senior teachers and teachers' professional performance. The study finally found that that the most prominent obstacles facing Islamic education teachers were related to administrative, technical and economic aspects. The study ended with recommendations to improve current practices in terms of teachers' preparation programs, diversified supervision, teachers' performance Islamic Education, and obstacles facing senior teachers; and recommendations for future research.